Rekomendasi Kebijakan Pemulihan Pariwisata Pasca Wabah Corona Virus Disease 2019 (Covid-19) di Kota Bandung - Dian Herdiana (Magister Tourism Study, Faculty of Tourism, Udayana University, 2020)
COVID-19 is a pandemic disease that has infected many cities in Indonesia, the impact caused by the spread of COVID-19 involves many aspects including economic, social, cultural, tourism and many more. Based on the problems mentioned above, this article is intended to describe the impact of COVID-19 on tourism in the city of Bandung which is one of the tourism city in the province of West Java, this article is also intended to recommend what policy should be made by the government of the Bandung City to restore tourism to the condition before the COVID-19 outbreak. This study uses a model building method with a descriptive analysis approach. The results revealed that tourism is one of the sectors most affected by the COVID-19 outbreak in the city of Bandung, efforts to restore tourism from COVID-19 must be comprehensive and sustainable. Bandung City Government and tourism entrepreneurs are demanded to carry out communication and coordination to develop tourism recovery policy instruments which include internal recovery efforts such as disaster management, organizational capacity building and external recovery efforts such as tourism relaxation policy and tourism promotion. Keywords: Village Tourism, Community, Empowerment, Development